Management of Information Systems (IntechOpen, 2018)
Management functions were developed first as a systematic step to carry out management activities, while implementation of the information components followed as part of management elements. The authors point out that the use of the possibilities and advantages of quantitatively supported managerial decisions gives managers the ability to quantify the impacts of both technical (hard) and subjective (soft) constraints and improve managerial decision-making processes that would otherwise be based mostly on personal intuition and experience. To achieve the goals and benefits of excellent performance, it is necessary to design and develop integrated models that would coordinate management functions and information system components as an integrated process. These facts are presented in various case studies.